Retrospective analysis of 15 cases of Penicillium marneffei infection in HIV-positive and HIV-negative patients. (April 2017) - Li, Yinyin; Lin, Zhongyuan; Shi, Xiang; Mo, Lijun; Li, Wenchao; Mo, Wuning; Yang, Zheng
Abstract: Penicillium marneffei ( P. marneffei ) causes systemic opportunistic infections in immunocompromised individuals, particularly in those infected with human immunodeficiency virus (HIV), and more rarely in HIV-negative patients. We retrospectively analyzed the cases of 15 patients infected with P. marneffei . The patients were divided into two groups: HIV-negative (n = 4) and HIV-positive (n = 11). Of the cases studied, three (75%) of the HIV-negative and six (55%) of the HIV-positive group had an accompanying lung infection. The ratio of CD4 + /CD8 + was 1.2 (SD = 0.99) in the HIV-negative group and 0.10 (SD = 0.095) in the HIV-positive patients. A series of laboratory examinations were performed and bone marrow smears were observed after staining. P. marneffei is a disseminated fungal infection associated with severe disease symptoms and high mortality rates. Our findings indicate that timely diagnosis and treatment by clinicians is crucial for preventing the spread of localized infections into systemic infections, thereby improving the prognosis of patients. Highlights: The clinical manifestations between HIV-negative and HIV-positive patients were similar. The incidence of P. marneffei infection in non-HIV-infected patients has increased. P. marneffei have a mold-like form at 25 °C and yeast-like form at 37 °C.